Lessons from the Investment Credit. - Seaman, James L. (The Accounting Review, 1965)
A considerable controversy has arisen during the past decade concerning the task of defining and codifying generally accepted principles of accounting. The efforts of the American Institute of Certified Public Accountants to narrow differences in the definition and application of accounting principles have become increasingly pronounced since the formation of the U.S. Accounting Principles Board in 1958. In 1963 the Board began a special research study to define accounting principles that might be said to enjoy current general acceptance. It is time that an integrated effort to develop accounting principles for and by the areas, which desperately need them, was accomplished. If the quest for these principles is to be satisfactorily consummated, it requires the abandonment of the artificial barriers to a combined effort. The accounting profession, regulatory authorities, specialized enterprises, investors, and American business all want and need a codification of accounting principles and reporting standards. It would appear reasonable that a task force comprised of these factions could command the unification of effort and of funds with which to get the job done.